Characterization of Human Breast Milk-Derived Limosilactobacillus reuteri MBHC 10138 with Respect to Purine Degradation, Anti-Biofilm, and Anti-Lipid Accumulation Activities - Jinhua Cheng; Joo-Hyung Cho; Joo-Won Suh (MDPI AG, 2024)
Background: Human breast milk is a valuable source of potential probiotic candidates. The bacteria isolated from human breast milk play an important role in the development of the infant gut microbiota, exhibiting diverse biological functions. Methods: In this study, Limosilactobacillus reuteri MBHC 10138 isolated from breast milk was characterized in terms of its probiotic safety characteristics and potential efficacy in hyperuricemia, obesity, lipid liver, and dental caries, conditions which Korean consumers seek to manage using probiotics. Results: Strain MBHC 10138 demonstrated a lack of D-lactate and biogenic amine production as well as a lack of bile salt deconjugation and hemolytic activity. It also exhibited susceptibility to common antibiotics, tolerance to simulated oral-gastric-intestinal conditions, and superior biological activity compared to three L. reuteri reference strains, including KACC 11452 and MJ-1, isolated from feces, and a commercial strain isolated from human breast milk. Notably, L. reuteri MBHC 10138 showed high capabilities in assimilating guanosine (69.48%), inosine (81.92%), and adenosine (95.8%), strongly inhibited 92.74% of biofilm formation by Streptococcus mutans, and reduced lipid accumulation by 32% in HepG2 cells. Conclusions: These findings suggest that strain MBHC 10138, isolated from human breast milk, has potential to be developed as a probiotic for managing hyperuricemia, obesity, and dental caries after appropriate in vivo studies.